Strong Ground Motions Generated by the February 11, 2014 Tatunshan Earthquake in the Taipei Metropolitan Area - Kou-Cheng Chen; Jeen-Hwang Wang; Kwang-Hee Kim; Pei-Ling Leu (Terrestrial, Atmospheric and Oceanic Sciences, 2014)

(untitled)
Strong-motion seismograms from the 11 February, 2014 Tatunshan earthquake were recorded at stations around the source area. These recordings were used to analyze the strong-motion characteristics in the area. The largest peak ground acceleration (PGA) values of 100.7, 93.4, and 66.6 cm sec-2 in the vertical, EW, and NS directions, respectively, were recorded at station TAP056, about 4.9 km to the northwest of the epicenter. The PGA decays fast with distance, indicating high attenuation in the Tatun volcanic area. The PGA ratio of vertical to horizontal ground motions decreases with increasing epicenter distance. The PGA values in the EW component are larger than those in the NS component. This might be associated with the focal mechanism of the earthquake. The spectral accelerations decrease rapidly with increasing period.